上顎に生じた腺性歯原性嚢胞の1例 - 楠川, 仁悟; 古賀, 真; 岩屋, 勝美; 原田, 真知子; 原口, 尚大; 岩本, 修 (日本口腔外科学会雑誌, 2012)
Glandular odontogenic cyst （GOC） is rare odontogenic cyst, first described by Gardener et al. in 1988. We report a case of GOC arising in the maxilla. The patient was 57-year-old man who presented with pain and swelling of the right canine region of the maxilla. Panoramic radiography showed a clearly bordered radiolucent region extending from the canine to premolar region of the maxilla. The clinical diagnosis was a radicular cyst of the canine teeth, and enucleation and tooth extraction were performed with the patient under general anesthesia. The histopathological diagnosis was GOC. As of 12 months after discharge, there has been no evidence of recurrence.